A Bibliometric Analysis of Activity-Based Management (ABM) Research Development Using Vosviewer: Management Accounting - Febriani, Erni (Klabat Accounting Review, 2024)
This study is a bibliometric visualization by taking journals through the publish or perish application with the scope of data in Scopus about Activity-Based Management (ABM) using the VOSviewer application. The purpose of the bibliometric analysis in this study is to determine; 1) the trend of development of publications related to activity-based management in developed countries each year, 2) the trend of Publication Journals, 3) collaboration between researchers with similar topics, 4) trend terms title and abstract and 5) trend terms author keywords. Data were collected from the Publish or Perish database published in 2010-2024 using the keyword "Activity Based Management". Then the author used VOSviewer software to analyze and visualize the database obtained. The results of the study showed that there were 172 articles discussing Activity Based Management. The year with the most research themes on Activity Based Management was 2010, which was 21 articles. Collaboration of researchers who collaborated included Joshua Aulda, Michael Hopea, Hubert Leya, Bo Xua and Kuilin Zhang. The publisher journal that published the most articles on the topic of "Activity Based Management" was Elsevier with 44 articles. Then Emerald published 34 articles over the past fourteen years.